Contemporary Waqf Companies from the Perspective of Islamic Economics: A Proposed Concept for the State of Kuwait (مجلة وقف في دراسات الاوقاف, 2026)
This study aims to conceptualize contemporary endowmentcompanies from an Islamic economic perspective, ensuring theirextend their benefits beyond an individual’s lifetime.The study also highlighted the precautions taken by Islamic lawto protect waqfs, emphasizing the importance of accurately managingtheir expenditures and regulating activities to ensure benefits,prevent harm, and avoid corruption. The research included areview of the current regulations and rules governing the supervisionof waqfs in the Kingdom of Saudi Arabia, and the judicial practicesfollowed as far as accessible. The study encompassed variousissues, benefits, and discussions that can be beneficial. Theresearcher recorded the key findings in the conclusion of the study.